METRICS FOR LEVERAGING MORE IN CLINICAL DATA MANAGEMENT: PROOF OF CONCEPT IN THE CONTEXT OF VACCINE TRIALS IN AN INDIAN PHARMACEUTICAL COMPANY - Bajpai N.; CHATTERJEE A.; DANG S.; SHARMA S.K. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The clinical trials data is of critical importance in providing evidence to support a drug or biologic product efficacy and safety. Quality data, productivityand lower product costs are key considerations in drug development process and to maintain competitive edge.Â Clinical Data Management(CDM) is a multistage process where various activities must be considered and decision taken in synergy and not sequentially; planned and executed according to the GCP (Good Clinical Practices) guidelines with highest standards.Â During the course of development, implementation and standardization of CDM procedures in the context of vaccine trialsin an Indian pharmaceutical company, it emerged that multi-factormetrics based performancemonitoring of critical procedural stepshave synergistic impact in boosting overall in-time progression of the projectand meeting desired data quality.It is important to acknowledge domain knowledge in developing performance metrics by involvingmembers of cross-functional teams. This report summarizes possible methodologies which if adopted are likely to keep the team members updated with the project advancement. The proof of concept,Â createdin the form of metrics designed to drive performance improvement through appropriate levels of internal controls and characterizing progress made under each criteria, is expected to improve overall productivity by accomplishing the aim with desired quality and within stipulated time-frameby mitigating the errors. Key-words: Clinical Data Management (CDM), Indian Good Clinical Practices(GCP), CDM Metrics